2015
DOI: 10.1161/circulationaha.114.012815
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “Postprocedural Aortic Regurgitation in Balloon-Expandable and Self-Expandable Transcatheter Aortic Valve Replacement Procedures: Analysis of Predictors and Impact on Long-Term Mortality: Insights From the FRANCE2 Registry”

Abstract: We thank Drs Iqbal and Serruys for their interesting comments on our study.1 Transcatheter aortic valve replacement is a very good alternative to conventional surgical replacement in patients with aortic stenosis at increased risk for surgery. 2,3 As efficient as it is, transcatheter aortic valve replacement has important limitations, including postprocedural aortic regurgitation (AR). Our study was designed to (1) describe the rate of postprocedural AR evaluated at discharge in a large series of consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
5
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 5 publications
(11 reference statements)
6
66
5
2
Order By: Relevance
“…The high frequency of valve‐in‐valve procedures might be related to two major factors. First of all, moderate aortic regurgitation was considered unacceptable in our study, as it has been reported to independently predict mid‐term mortality . Therefore, in cases with persistent moderate or severe aortic regurgitation after several attempts of postdilation, we always chose to implant a second valve.…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency of valve‐in‐valve procedures might be related to two major factors. First of all, moderate aortic regurgitation was considered unacceptable in our study, as it has been reported to independently predict mid‐term mortality . Therefore, in cases with persistent moderate or severe aortic regurgitation after several attempts of postdilation, we always chose to implant a second valve.…”
Section: Discussionmentioning
confidence: 99%
“…In the French Aortic National CoreValve and Edwards registry, 16 those patients with postprocedural aortic regurgitation !2þ were associated with higher risk for 1-year mortality. It appears that there is no association of mild aortic regurgitation after TAVI with short-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In several large registries, moderate or higher PVR but not mild PVR was shown to have a significant impact on survival. 13,14 In the meta-analysis by Athappan and colleagues, 17 mild PVR was associated with a 1.9-fold increase in mortality, but this association was not confirmed in sensitivity analysis. Several factors may explain the intriguing association between mild PVR and mortality including (i) the difficulty of grading PVR and the possibility that it may have been underestimated in a substantial number of patients and (ii) the worse baseline risk profile of patients with mild PVR versus those with none or trace PVR.…”
Section: Impact Of Paravalvular Regurgitation On Outcomesmentioning
confidence: 99%
“…29,30 Several nonrandomized studies have reported a greater incidence of PVR with the self-expanding CoreValve versus the balloon expandable SAPIEN valve. 14,17,33,34 In a recent meta-analysis, the incidence of moderate or severe PVR was 16% with the CoreValve versus 9% for the SAPIEN (P 5 .005). The randomized, controlled trial CHOICE confirmed that moderate/severe PVR is more frequent with the CoreValve compared with the SAPIEN (18.3% vs 4.1%; P<.001).…”
Section: Incidence and Predictors Of Paravalvular Regurgitationmentioning
confidence: 99%